2017
DOI: 10.1186/s12941-017-0192-2
|View full text |Cite
|
Sign up to set email alerts
|

Killing of Serratia marcescens biofilms with chloramphenicol

Abstract: Serratia marcescens is a Gram-negative bacterium with proven resistance to multiple antibiotics and causative of catheter-associated infections. Bacterial colonization of catheters mainly involves the formation of biofilm. The objectives of this study were to explore the susceptibility of S. marcescens biofilms to high doses of common antibiotics and non-antimicrobial agents. Biofilms formed by a clinical isolate of S. marcescens were treated with ceftriaxone, kanamycin, gentamicin, and chloramphenicol at dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…This adherent nature of S. marcescens utilizes living as well as non-living surfaces such as biomedical devices to form the biofilm, finally leads to life-threatening infections 5 . A recent report states that biofilms produced by S. marcescens clinical isolates require supratherapeutic doses of kanamycin, gentamicin and chloramphenicol as minimum inhibitory concentration, which is 10, 100 and 1000 times higher concentration respectively, to kill the planktonic cells 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This adherent nature of S. marcescens utilizes living as well as non-living surfaces such as biomedical devices to form the biofilm, finally leads to life-threatening infections 5 . A recent report states that biofilms produced by S. marcescens clinical isolates require supratherapeutic doses of kanamycin, gentamicin and chloramphenicol as minimum inhibitory concentration, which is 10, 100 and 1000 times higher concentration respectively, to kill the planktonic cells 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that S. marcescens is able to develop biofilm associated with either biotic or abiotic surfaces (31)(32)(33)(34). This ability is associated with the capacity of Serratia to colonize and persist in medical devices, such as catheters or prostheses (35), and to enhance bacterial resistance to antibiotics (36).…”
mentioning
confidence: 99%
“…Hume et al found that S. marcescens bacteria endowed with biofilm and colonizing a contact lens could resist phagocytosis [57], and it is not surprising that they are also more resistant to antibiotics. Ray et al [58] investigated the susceptibility of S. marcescens biofilm to high doses of common antibiotics (ceftriaxone, kanamycin, gentamicin, and chloramphenicol) and other non-antimicrobial agents, and concluded that only chloramphenicol reduced biofilm biomass and viability. Furthermore, another study [59] has demonstrated that chloramphenicol can act synergistically with the antimicrobial peptides (AMPs), such as FK-13-a1 and FK-137, to reduce the bacterial biofilm produced by multidrug-resistant P. aeruginosa , vancomycin-resistant E. faecalis , and MRSA.…”
Section: Role Of Biofilm In Eye Infectionsmentioning
confidence: 99%